2014
DOI: 10.1002/2014jd021688
|View full text |Cite
|
Sign up to set email alerts
|

Further development of a parameterization for convective turbulent dust emission and evaluation based on field observations

Abstract: Further developments of a parameterization scheme for convective turbulent dust emission (CTDE) are presented. The scheme is advanced by including (1) a new statistical description of instantaneous momentum flux, (2) a correction function for cohesive force to account for the effect of soil moisture, and (3) a correction function for lifting force to consider the effect of vegetation roughness elements. The probability density function describing instantaneous momentum flux is now derived from large-eddy simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 57 publications
3
69
0
Order By: Relevance
“…They are combined with a characterisation of surface properties, where properties and relations are to different degrees empirical (source functions) or deduced from microphysical processes. The dominant processes considered are saltation bombardment by sand blasting and aggregate disintegration, and more elaborate emission schemes consider additional effects such as direct aerodynamic entrainment (Shao, 2001;Klose et al, 2014). The inability of most current global models to resolve convection means that haboobs, which are responsible for a major fraction of the dust emissions (Marsham et al, 2013;Allen et al, 2013Allen et al, , 2015, are not represented at all.…”
Section: K Klingmüller Et Al: Revised Mineral Dust Emissions In Emacmentioning
confidence: 99%
“…They are combined with a characterisation of surface properties, where properties and relations are to different degrees empirical (source functions) or deduced from microphysical processes. The dominant processes considered are saltation bombardment by sand blasting and aggregate disintegration, and more elaborate emission schemes consider additional effects such as direct aerodynamic entrainment (Shao, 2001;Klose et al, 2014). The inability of most current global models to resolve convection means that haboobs, which are responsible for a major fraction of the dust emissions (Marsham et al, 2013;Allen et al, 2013Allen et al, , 2015, are not represented at all.…”
Section: K Klingmüller Et Al: Revised Mineral Dust Emissions In Emacmentioning
confidence: 99%
“…Shao et al, 2011;Kok et al, 2014;Klose et al, 2014) are in general more sophisticated than what is described above and include a dust emission scheme, the estimate of Q is essentially done using Eqs. (1) to (3) or similar.…”
Section: Introductionmentioning
confidence: 99%
“…Dust emission by direct aerodynamic entrainment is not considered in saltation-based global/regional dust models [e.g., Zender et al, 2003], although some models [e.g., Gillette and Passi, 1988;Ginoux et al, 2001] account for the dust emitted by both mechanisms in terms of surface wind velocity. Several studies, however, have shown that under certain conditions, for example, in fine soils without crust [Loosmore and Hunt, 2000], silty agricultural soil [Kjelgaard et al, 2004], supply-limited desert surfaces [Macpherson et al, 2008], loess deposits [Sweeney and Mason, 2013], and under convective turbulence [Klose et al, 2014], the primary mechanism for dust emission is aerodynamic entrainment rather than sandblasting. In this work, we compare emitted dust concentrations and particle size distributions (PSD) in sandblasting to those in direct aerodynamic entrainment for a range of friction velocities in an attempt to understand the dynamics of dust emission in these two processes.…”
Section: Introductionmentioning
confidence: 99%